Instructor Satisfaction in University of California Extension’s On-line Writing Curriculum - Almeda, Mary Beth; Rose, Kathleen (Online Learning, 2000)
This article describes instructor satisfaction in 14 online courses in freshman-level composition and literature, business writing, and English as a Second Language offered in the University of California (UC) Extension’s online program. The courses chosen for this case study reflect UC Extension’s entire ALN program, in that they comprise a broad selection of college- and professional-level courses organized in course sequences and certificate programs. The paper reviews UC Extension’s ALN program, describes course and instructor selection criteria, and discusses such issues as course production and costs, instructor support, the transfer of teaching skills, instructor computer literacy, and instructor compensation. The results of an informal instructor survey also are discussed. Obstacles to adoption, effective and problematic practices, and critical programmatic and individual course factors gleaned from this analysis are outlined.